2005
DOI: 10.1892/0891-6640(2005)19<93:mosiif>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Serum IgG in Foals by Radial Immunodiffusion and Automated Turbidimetric Immunoassay

Abstract: Hypogammaglobulinemia as a result of failure of transfer of passive immunity (FTPI) is an important risk factor for infectious disease in neonatal foals. The current gold standard for determining serum immunoglobulin concentrations is radial immunodiffusion (RID). The purpose of this study was to compare immunoglobulin concentrations measured by RID with those determined by an automated turbidimetric immunoassay (TIA), which has a much shorter turnaround time. Immunoglobulin concentrations were measured by bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
55
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(68 citation statements)
references
References 8 publications
(19 reference statements)
9
55
2
2
Order By: Relevance
“…The latter test is effective in assessing a foal with IgG concentrations<400 mg/dl and<800 mg/dl when the cutoff value is set to 6% and 10%, respectively. Both tests are as accurate as other commercially available test kits reported by a previous study [12]. The results particularly suggest that the measurement of DVRI is quite useful in assessing FPT in foals as an initial screening test "stall-side" because it has a relatively high NPV, and of more importance, it is procedurally easier to perform, allows for rapid interpretation and is more cost-effective than any other commercially available test kit.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…The latter test is effective in assessing a foal with IgG concentrations<400 mg/dl and<800 mg/dl when the cutoff value is set to 6% and 10%, respectively. Both tests are as accurate as other commercially available test kits reported by a previous study [12]. The results particularly suggest that the measurement of DVRI is quite useful in assessing FPT in foals as an initial screening test "stall-side" because it has a relatively high NPV, and of more importance, it is procedurally easier to perform, allows for rapid interpretation and is more cost-effective than any other commercially available test kit.…”
Section: Discussionmentioning
confidence: 57%
“…Measuring STP is an indirect way to estimate the IgG concentration and is based on the assumption that low STP after nursing colostrum reflects a failure in transfer of maternal antibodies [18]. On the other hand, several studies have suggested that STP concentrations using a cutoff value of<4.6 or 4.7 g/dl are likely to indicate FPT and that measurement of the STP concentration might be used as a guide to assess the IgG concentration if no other test is available or as an adjunctive test [12,46]. In this study, the STP concentration was significantly correlated with the serum IgG concentration (r=0.86), which confirms the results obtained in a previous study (r=0.85) [41].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations